2022
DOI: 10.1186/s43055-022-00741-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic accuracy of visual lung damage computed tomography score for mortality prediction in patients with COVID-19 pneumonia: a systematic review and meta-analysis

Abstract: Background Chest computed tomography (CT) findings provide great added value in characterizing the extent of disease and severity of pulmonary involvements. Chest CT severity score (CT-SS) could be considered as an appropriate prognostic factor for mortality prediction in patients with COVID-19 pneumonia. In this study, we performed a meta-analysis evaluating the prognostic accuracy of CT-SS for mortality prediction in patients with COVID-19 pneumonia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…A recent meta-analysis study showed that CT-SS index with and without an optimal cutoff was positively associated with mortality of COVID-19 patients (OR 7.124; 95% CI 5.307–9.563 and OR 1.244; 95% CI 1.157–1.337, respectively) [ 17 ]. Sensitivity, specificity, and AUC of this predictive parameter were 0.67 (95%CI: 0.59–0.75), 0.79 (95%CI: 0.74–0.84), and 0.8248, respectively [ 16 ]. Although the association between CT-SS and mortality of COVID-19 patients was reported [ 16 , 17 ], its prognosis significance in combination with other prognostic parameters was not evaluated yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis study showed that CT-SS index with and without an optimal cutoff was positively associated with mortality of COVID-19 patients (OR 7.124; 95% CI 5.307–9.563 and OR 1.244; 95% CI 1.157–1.337, respectively) [ 17 ]. Sensitivity, specificity, and AUC of this predictive parameter were 0.67 (95%CI: 0.59–0.75), 0.79 (95%CI: 0.74–0.84), and 0.8248, respectively [ 16 ]. Although the association between CT-SS and mortality of COVID-19 patients was reported [ 16 , 17 ], its prognosis significance in combination with other prognostic parameters was not evaluated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity, specificity, and AUC of this predictive parameter were 0.67 (95%CI: 0.59–0.75), 0.79 (95%CI: 0.74–0.84), and 0.8248, respectively [ 16 ]. Although the association between CT-SS and mortality of COVID-19 patients was reported [ 16 , 17 ], its prognosis significance in combination with other prognostic parameters was not evaluated yet. Therefore, in this study, kNN, MLP, SVM, and J48 decision tree algorithms were developed based on the most relevant features in determining the risk of COVID-19 mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study based on similar features, AUC values ranging between 0.84 and 0.89 were obtained with the XGBoost model, which is an advanced version of the GB model [ 21 ]. Zakariaee et al added CT parenchyma score to the dataset consisting of demographics, clinical data, comorbid diseases, and laboratory results [ 22 ]. In the study comparing kNN, multilayer perceptron, SVM, and J48 decision tree algorithms, an AUC of 0.97 was obtained with the kNN model, and it was observed that the addition of CT parenchyma score improved model performance.…”
Section: Discussionmentioning
confidence: 99%
“…CT severity score (CT-SS) is determined according to the extent of lung involvement on the CT images and is an appropriate prognostic factor for mortality prediction in patients with COVID-19 pneumonia. 8 In Cao Y et al study 9 , it was reported that deceased patients had higher CT-SSs than discharged patients (20.9 ± 3.0 vs. 15.6 ± 5.0, p < 0.001). Similar results were also observed in several countries.…”
mentioning
confidence: 93%